PREDICTIVE VALUE OF MOTOR ABILITIES IN RELATION TO KARATE TECHNIQUE - Ivica Šćepanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The aim of this study was to determine the influence of basic motor abilities on execution speed of complex karate combination. The sample of subjects included 37 male karate practitioners aged 15 years ± 6 months from three karate clubs from the north of Montenegro. For the purposes of this study a system of 19 variables, which are hypothesized to cover areas of motor abilities (18 variables) and specific motor abilities (1 variable), was used. The data obtained in this study were submitted to statistical analysis, which involves regression analysis as the primary statistical operation. Insight into the results indicate that the system of basic motor abilities has a statistically significant influence on the speed of execution of a complex karate combination (R=.92; R2=.85; Q=.00). A significant effect of the individual predictors on the aforementioned criteria remained in the domain of variables for assessment of running speed and coordination: 20m running start (β=-.41; Q-β=.02), side steps (β=.44; Q-β=.02) and agility in the air (β=.61; Q-β=.02).